2015
DOI: 10.1021/acs.analchem.5b03291
|View full text |Cite
|
Sign up to set email alerts
|

Collision Induced Unfolding of Intact Antibodies: Rapid Characterization of Disulfide Bonding Patterns, Glycosylation, and Structures

Abstract: Monoclonal antibodies (mAbs) are among the fastest growing class of therapeutics due to their high specificity and low incidence of side effects. Unlike most drugs, mAbs are complex macromolecules (∼150 kDa), leading to a host of quality control and characterization challenges inherent in their development. Recently, we introduced a new approach for the analysis of the intact proteins based on ion mobility-mass spectrometry (IM-MS). Our protocol involves the collision induced unfolding (CIU) of intact antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
244
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(263 citation statements)
references
References 43 publications
18
244
1
Order By: Relevance
“…We found that engineered covalent links between core and dimer domain restricts unfolding of NapA. Notably, the introduction of a disulphide bond in of itself does not restrict gas-phase unfolding in other protein systems25, implying that the covalent linkages used here are influencing specific unfolding events in NapA. These restricted unfolding results imply that the core domains in the native protein are almost certainly flexibly attached, and these interactions are disrupted during gas-phase activation.…”
Section: Discussionmentioning
confidence: 80%
“…We found that engineered covalent links between core and dimer domain restricts unfolding of NapA. Notably, the introduction of a disulphide bond in of itself does not restrict gas-phase unfolding in other protein systems25, implying that the covalent linkages used here are influencing specific unfolding events in NapA. These restricted unfolding results imply that the core domains in the native protein are almost certainly flexibly attached, and these interactions are disrupted during gas-phase activation.…”
Section: Discussionmentioning
confidence: 80%
“…By following the gas phase unfolding pattern of protein ions, the unfolding “heat maps” [41] are a function of protein higher order structure and protein-ligand binding state [39, 42, 5355]. Both intact OCP and NTD undergo gas phase unfolding to increase their CCS, whereas CTD remarkably undergoes no significant unfolding (see Figure 5 for maps of intact OCP monomer, dimer, OCP NTD and CTD).…”
Section: Resultsmentioning
confidence: 99%
“…For example, ion mobility (IM) can be coupled with MS to obtain collision cross sections, yielding information about overall molecular shape [3][4][5][6][7][8]. Collision induced unfolding has recently proven to be valuable in distinguishing antibody isoforms by comparing "fingerprint plots" generated by differences in unfolding of the isoforms in an ion trap prior to IM-MS analysis [9]. Ion-ion reactions can be used to assign charge states in very large systems [10].…”
mentioning
confidence: 99%